Cómo desarrollar la ciencia y tecnología en los países atrasados: una mirada en prospectiva - Dejo Soto, Federico (2003)
The present work exposes in the author's opinion which are the necessary conditions that must converge to make possible a permanent impulse to the scientific and technological development in the backward countries. The central idea is that the development of science and technology depends on the possibilities of change and progress of other sectors of the economic social and cultural life of a country. Among these conditions are analysed education industrial development the link with the needs of the economy and the well-being of the population the dignified retribution to the scientist the emergence of a critical mass of scientists starting from the already advanced the mass use of information technologies and policy to support publications.